Public cowboy no. 1 the life and times of Gene Autry - George-Warren, Holly (Oxford University Press, 2007)
The only performer to earn five stars on the Hollywood Walk of Fame--for film, recordings, television, radio, and live performance--Gene Autry was the singing cowboy king. Journalist George-Warren offers the first serious biography, tracing Autry's climb from farm boy to multimillionaire. Autry's loving mother died on the brink of her son's success, while his ne'er-do-well father married five times and wandered the West. Autry battled his own demons but emerges here as one of America's most charitable benefactors, known for his boundless generosity, and a patriot who enlisted during World War II. The book provides colorful details of Autry's lengthy radio and recording career; his movie career, where he breathed new life into the Western genre; and his role in early television, the first movie star to develop his own TV shows. Along the way, he invested shrewdly, becoming the only entertainer listed among 1990's Fortune 400.--From publisher description.